The Effectiveness of Baby Spa Education in Improving Mothers' Knowledge and Practices in Managing Acute Respiratory Infections (ARI) in Toddlers in Lingsar Village - YASIR, LALU; Aryani, Ni Putu; Zubair, M. Abdul Hamid; Salfarina, Anna Layla; Ningsih, Husma Eka (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2025)
Introduction: Acute Respiratory Infections (ARI) are a leading cause of morbidity and mortality in children under five in Indonesia, often exacerbated by low parental knowledge and unfavorable environmental conditions. This community service initiative aimed to address this issue in Lingsar Village, West Lombok, by introducing Baby Spa—a complementary therapy involving infant massage and hydrotherapy—as a measure to improve respiratory hygiene and overall infant health, thereby aiding in the management of ARI. Methods: The intervention was conducted through an educational session and a practical demonstration of Baby Spa techniques. A total of 20 mothers of toddlers with a history of ARI participated in the program. The participants' knowledge and practices regarding ARI management were assessed using a pre-test and post-test questionnaire. Results: The activity demonstrated a significant improvement in the mothers' knowledge and reported practices. The proportion of mothers with good knowledge increased from 10% (pre-test) to 85% (post-test). Similarly, the percentage of mothers demonstrating positive practices for managing ARI in their toddlers rose from 40% to 75% following the intervention. Conclusion: Educational intervention on Baby Spa proved to be highly effective in enhancing maternal knowledge and practices related to ARI management in this community. This approach presents a promising, relevant, and acceptable promotive and preventive strategy that can be integrated into broader public health efforts to reduce the burden of ARI in rural settings.